Impact of Root and Tuber Expansion Programme Technology Adoption on Poverty and Food Security Status of Cassava- Farming Households in Southwestern Nigeria (2011)
Adoption of yield increasing technologies among farming households is one way of reducing poverty and food insecurity. In Nigeria, Root and Tuber Expansion Programme (RTEP) was implemented to develop improved technology of root and tuber crops. However, the impact of RTEP technology on poverty and food security has not been fully established. Therefore, the effect of RTEP technology on poverty and food security status of cassava-farming households in southwestern Nigeria was investigated. Ondo and Ogun states were randomly selected from the six states in southwestern Nigeria. Two RTEP participating and two Non-RTEP participating Local Government Areas (LGAs) were randomly chosen from each state. Three communities were randomly selected from each of the LGAs. In each RTEP community, 30 households were randomly selected (beneficiaries and non-beneficiaries) while 15 households were randomly selected from each Non-RTEP community making 540 respondents. Data were collected on age, gender, Household Size (HS), Land Area Cultivated (LAC), technology adoption, Credit Accessibility (CA), Educational Level (EL), Off-farm Activities Participation (OAP), Cassava Yield (CY), Distance to Input Market (DIM) and Household Consumption Expenditure (HCE) using structured questionnaire. The HCE was used to estimate Poverty Incidence (PI) and Food Insecurity Incidence (FII) while other variables were hypothesized to influence Adoption Level (AL) of RTEP technology. Data were analyzed using propensity score matching, descriptive statistics, Foster-Greer-Thorbecke and Tobit regression model at p = 0.05. There were 387 RTEP and Non-RTEP households with similar characteristics. Age (44.3 ± 10.1 years), HS (6.0 ± 2.0) and LAC (1.0 ± 0.4 hectares) of the beneficiaries were not significantly different from those of the non-beneficiaries. The AL of RTEP technology was 76.01%. Cassava yield of RTEP Beneficiaries (RTEPB) was 14.56 ± 1.27 tons/ha. Gender, OAP, CA and EL significantly increased AL by 13.8%, 15.8%, 4.7% and 17.6% respectively while DIM decreased AL by 1.8%. At poverty and food insecurity lines of ₦34,473.00 and ₦20,132.20 respectively per annum, 55.0% RTEPB were poor while 51.3% were food insecure. The RTEP technology adoption reduced PI of RTEPB by 11.2%. The PI of the male beneficiaries reduced by 12.6% compared with 5.6% for female. The PI of RTEPB with CA reduced by 11.8% compared with 5.2% for those without CA. The PI decreased by 14.1% for RTEPB with OAP while the reduction was 8.2% for those without off-farm activity. The FII decreased by 16.3% with male RTEPB having higher reduction of 17.8% compared with female of 8.0%. The FII of the beneficiaries with CA decreased by 20.9% while the reduction was 9.8% for those without CA. The decrease in FII was 17.45% for RTEPB with OAP compared to 9.4% for those not participating. Root and Tuber Expansion Programme technology alleviated both poverty and food insecurity status of beneficiaries especially among males, those with credit accessibility and off-farm activity participation in southwestern Nigeria.